Including medium effects and longer temporal scales in TRAX-CHEMxt - Camazzola, Gianmarco; Boscolo, D; Abram, V; Scifoni, E; Dorn, Alexander; Durante, M; Krämer, M; Fuss, M C (Physics in medicine and biology, 2025)
Objective. Radiation biophysical modelling of the spatio-temporal events following energy deposition in a tissue-like medium is a useful tool for investigating mechanistic features of radiobiological processes. The present study focuses on the description of complex milieux and long time domains. Approach. Monte Carlo (MC) chemical track structure algorithms allow the formation, transport, and recombination of radical species under various irradiation conditions to be followed. This feature has been proposed to have outermost relevance, e.g. in the comprehension of the FLASH effect. Nevertheless, to extend the simulations predictability range in both temporal scales and realistic environments, while avoiding prohibitive running times, computationally lighter approaches have to be used in combination with the accurate step-by-step descriptions provided by MC. To this end, TRAX-CHEMxt has been implemented. Main results. We propose here an upgraded version of the code, capable now to investigate the chemical effects of radiation up to 1 s and in a more complex environment, featured not only by oxygenated water, but also by a representative biomolecule, RH, and an antioxidant component, XSH. The robustness of the code in this new configuration has been proven. Its predictions are compared with both full MC counterparts at the overlapping time scale, (1-10) µs, and available experimental data at longer temporal points, showing in all cases good agreements. The change in the chemical yields due to the presence of RH and XSH is then investigated, as a function of primary particle type, energy, LET, and target oxygenation. Significance. TRAX-CHEMxt can thus be effectively applied to study the impact of radiation-induced radicals at larger time scales on more complex systems, allowing for specific biological targets simulations.
Veröffentlicht: 18. Dezember 2025
Gesehen am 16.02.2026